The Competition Between Processing and Discourse-Pragmatic Factors in Children's and Adults' Production of Adverbial When-Clauses. - Shijie Zhang; Junge, Bianca; Lieven, Elena; Brandt, Silke; Theakston, Anna (Journal of Speech, Language & Hearing Research, 2023)
Purpose: This is the first study to investigate the combined effects of processing-based factors (i.e., clause length and clause order) and discourse-pragmatic factors (i.e., information structure) on children's and adults' production of adverbial when-clauses. Method: In a sentence repetition task, 16 three-year-old and 16 five-year-old children as well as 17 adults listened to and watched an animated story and then were asked to repeat what they had just heard and seen. Each story contained an adverbial when-clause and its main clause. The sentences were manipulated for their clause order, information structure, and clause length. Results: Adults tended to change main--when clause orders to when--main in their repetitions, and they showed a strong preference for the given--new order of information. In contrast, 3-year-olds tended to change when--main clause orders to main--when, and they showed a preference for the new--given order of information. In addition, 3-year-olds tended to produce short--long clause orders irrespective of what they had heard, whereas adults produced both short--long and long--short orders in line with the input. In general, 5-year-olds were more adultlike in their production compared to 3-year-olds. Conclusions: Young children were strongly affected by processing-based factors in their production of complex sentences. They tended to order main and when-clauses in a way that requires less planning and processing load. However, they have not yet attained an adultlike sensitivity to discourse-pragmatic factors. Supplemental Material: https://doi.org/10.23641/asha.24422635